Pengaruh Kebiasaan dan Intensitas Belajar terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Bella, Sinta; Nursupiamin, Nursupiamin; Yulia, Yulia (Jurnal Pendidikan Matematika : Judika Education, 2026)
This study aims to analyze the effect of study habits and learning intensity on students’ mathematical problem-solving ability. The research employed a quantitative approach with an ex post facto design involving eleventh-grade students of MAN 2 Palu in the 2025/2026 academic year. The results showed that the Nagelkerke Pseudo R-Square value of 0.093 indicates that study habits and learning intensity only explain 9.3% of the variance in students’ mathematical problem-solving ability. Study habits and learning intensity have a positive and significant relationship with students’ mathematical problem-solving ability, although the strength of the relationship is relatively weak. This finding suggests that mathematical problem-solving ability is influenced by various other factors beyond the learning behaviors examined in this study.   Keywords: Learning Intensity, Learning Habits, Mathematical Problem Solving Ability,